Business Process Improvement Melalui Pengembangan Teknologi Informasi Pada UMKM Tangan Diatas Kota Batam - Diah Amalia; Shinta Wahyu Hati; Dwi Amalia Purnamasari; Banu Failasuf; Jessica Olifia; Vina Kholisa Dinuka; Fandy Bestario Harlan (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2023)
The purpose of the research is to adjust and apply inventory planning in accounting and inventory control, to identify and evaluate inventory management problems as well as making a Web-Based Goods Inventory Application Prototype in the culinary field of Batam City TDA. The research method is a qualitative approach method and the Business Process Improvement Framework method and a Web-Based Goods Management Application Prototype using the Waterfall model. The process of collecting data through surveys and interviews. The research results are (1) the application of the inventory recording method has not used the perpetual method. The respondent's inventory valuation method uses the First in First out Method. Inventory measurement for respondents only recorded the cost of purchasing inventory so that it was not in accordance with PSAK No.14. Disclosure of inventories to respondents is presented in the financial statements, namely the balance sheet and income statement so that they are in accordance with PSAK No.14 (Revised 2015); (2) In the operational management of inventory in the warehouse, there are business processes for requesting goods in the Warehouse that are still not effective, business processes for receiving raw materials that are not yet effective and optimal, business processes for returning materials or goods from warehouses to suppliers due to non-conformance of goods, and sales business processes materials to users who are not yet effective. Researchers compile and submit Warehousing Operational Standards, it is hoped that the management from Curry Up, Jomtri, Baabaa Kambing can implement the SOP; (3) Researchers create a Web-Based Inventory Application Prototype using the Waterfall model with the stages of needs analysis and system design.